2011
DOI: 10.1088/1741-2560/8/3/036010
|View full text |Cite
|
Sign up to set email alerts
|

Fast attainment of computer cursor control with noninvasively acquired brain signals

Abstract: Brain-computer interface (BCI) systems are allowing humans and non-human primates to drive prosthetic devices such as computer cursors and artificial arms with just their thoughts. Invasive BCI systems acquire neural signals with intracranial or subdural electrodes, while noninvasive BCI systems typically acquire neural signals with scalp electroencephalography (EEG). Some drawbacks of invasive BCI systems are the inherent risks of surgery and gradual degradation of signal integrity. A limitation of noninvasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 22 publications
7
84
1
1
Order By: Relevance
“…To assess a potential contribution of the movement of the eyes to decoding, the decoding process was also carried out by adding the standardized vertical electrooculogram (VEOG) activity to the optimal set of electrodes used for decoding (Bradberry et al 2011). The r values and the regression weights were calculated in this new condition.…”
Section: Methodsmentioning
confidence: 99%
“…To assess a potential contribution of the movement of the eyes to decoding, the decoding process was also carried out by adding the standardized vertical electrooculogram (VEOG) activity to the optimal set of electrodes used for decoding (Bradberry et al 2011). The r values and the regression weights were calculated in this new condition.…”
Section: Methodsmentioning
confidence: 99%
“…Many BMI training paradigms involve an initial period of parameter tuning. In this period, parameters of a neural signal model are adjusted to relate observed neural signals with overt movements (Santhanam, Ryu, Yu, Afshar, & Shenoy, 2006;Serruya, Hatsopoulos, Paninski, Fellows, & Donoghue, 2002), or instructed motor imagery (Bradberry, Gentili, & Contreras-Vidal, 2011;Hochberg et al, 2006;Kim, Simeral, Hochberg, Donoghue, & Black, 2008). During this initial period, the user is not directly operating the BMI.…”
Section: Definition and Categorization Of Naive Adaptive Brain-machinementioning
confidence: 99%
“…These stages can be reversed. The design philosophy underlying lockstep estimation, called certainty equivalence, is the pervasive approach in BMI algorithm design, including all methods based on training data that use overt movements (Santhanam et al, 2006;Serruya et al, 2002), or instructed motor imagery (Bradberry et al, 2011;Hochberg et al, 2006;Kim et al, 2008), as well as previously developed naive adaptive control methods Gage et al, 2005;Orsborn et al, 2012). Certainty equivalence means that when parameters are estimated, the current estimate of intent is assumed to be the true intent (i.e., equivalent to being known with certainty), and vice versa (Bertsekas, 2005).…”
Section: Joint Estimation Versus Lockstep Estimationmentioning
confidence: 99%
“…Thus, the next step is to decode imagined movements. Bradberry et al [12] showed already the control of a computer cursor with imagined movements, but the conclusiveness of the results is questionable [13].…”
Section: Introductionmentioning
confidence: 99%